2016
DOI: 10.1021/acs.jpcc.6b01725
|View full text |Cite
|
Sign up to set email alerts
|

Poly(bisphenol) Polymers as Passivating Agents for Carbon Electrodes in Ionic Liquids

Abstract: Poly(bisphenol) polymers are identified as a new class of passivating agents for carbon electrodes in ionic liquids. They are inert and can readily be deposited as thin, conformal films by electropolymerization. Unlike conventional poly(monophenol) polymers, a single voltammetric scan is sufficient to accomplish their deposition. This is seen, for example, in the cases of poly(bisphenol A) and poly(bisphenol P). In each case, the thickness of the electropolymerized films is determined by the quantum tunneling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…It has also been shown that phenolic compounds with hydroxyl groups in the meta-position tend to form polymers instead of quinones producing reduced electroactivity. 25 The number of hydroxyl groups seems to be not critical for the electrochemical behaviour since phenol and phloroglucinol presented similar trends. In addition to the known electrochemical behaviours of different phenolic compounds, our results suggest also that the compounds with reversible or quasireversible redox behaviour and with more stable oxidation products are more sensitive to the composition of the electrode surface since a little change in the amount of oxygen functionalities can generate significant alteration to their oxidation potential.…”
Section: Resultsmentioning
confidence: 97%
“…It has also been shown that phenolic compounds with hydroxyl groups in the meta-position tend to form polymers instead of quinones producing reduced electroactivity. 25 The number of hydroxyl groups seems to be not critical for the electrochemical behaviour since phenol and phloroglucinol presented similar trends. In addition to the known electrochemical behaviours of different phenolic compounds, our results suggest also that the compounds with reversible or quasireversible redox behaviour and with more stable oxidation products are more sensitive to the composition of the electrode surface since a little change in the amount of oxygen functionalities can generate significant alteration to their oxidation potential.…”
Section: Resultsmentioning
confidence: 97%
“…We attribute the incomplete passivation to the large surface area and porous features of the eroded 3D-printed surfaces. Although passivating films have shown interesting properties for corrosion protection, [47][48][49] catalysis 50 and as permselective membranes in biosensor research, 46 the formation of such films has its drawbacks for electrochemistry. A few examples include the interference of electrode passivation with the electrochemical treatment of phenolic wastes, as well as with electrochemical immunoassay schemes.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies [46,47] have shown that oxidation of compounds containing quinone or phenol groups may give rise to the formation a polymer film on the electrode surface, which could impede electron transference at the electrode/solution interface. This phenomenon was observed during the investigation of rutin oxidation on a glassy carbon electrode using cyclic, differential pulse and square wave voltammetries [40], thereby rendering the use of the flavonoid as an electrochemical mediator somewhat problematic.…”
Section: Influence Of Rutin Concentration On the Oxidation Of Captoprilmentioning
confidence: 99%